2003
DOI: 10.1207/s15327590ijhc1502_4
|View full text |Cite
|
Sign up to set email alerts
|

Testing Visual Search Performance Using Retinal Light Scanning as a Future Wearable Low Vision Aid

Abstract: For the goal of designing a wearable low vision aid, aspects of both head-mounted display (HMD) design and performance evaluation were integrated into a single study of scanning ability. A head-mounted version of a novel retinal light scanning display known as the virtual retinal display was fabricated for this study. A remote head CCD (charge coupled device) attached approximately at the user's line of sight was used as the input source. Scanning ability was quantified as the time to identify a target in a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Typically, the experiments involved only a small number of people with LV (the mean sample size in all studies was just 16, and the mean sample size of participants with LV was 10). Some studies simulated LV in people with normal vision using occlusion foils, 45 diffuser films, 60,67 or by avoiding using optical corrections 81 to reduce VA and CS and simulate tunnel vision. 72 Although these low vision simulations can be useful, they cannot simulate other visual problems, such as light sensitivity, color vision impairment, or patchy vision.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the experiments involved only a small number of people with LV (the mean sample size in all studies was just 16, and the mean sample size of participants with LV was 10). Some studies simulated LV in people with normal vision using occlusion foils, 45 diffuser films, 60,67 or by avoiding using optical corrections 81 to reduce VA and CS and simulate tunnel vision. 72 Although these low vision simulations can be useful, they cannot simulate other visual problems, such as light sensitivity, color vision impairment, or patchy vision.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the participants looked at a section of the scene shown in Experiment 1, composed of a desk with rails on it, for 6 s. This time length was chosen because it has been shown that 4 to 8 s are enough to encompass a 3D visual scene (Lin et al, 2003;Blackmon et al, 1997). This section of the scene combined the video view with the photorealistic virtual model, realizing the different variations regarding augmentation of the virtual view, transition, and reprojection error in the stationary way mentioned above.…”
Section: Methodsmentioning
confidence: 99%
“…The small mirror inset or see-through beamsplitter design allows the displayed icon to augment the user's vision. The high-brightness of the laser diode or future LED source make this display suitable for use in outdoor conditions with these various display modes [9].…”
Section: Scanning Fiber Displaymentioning
confidence: 99%